Prevalence and Risk Factors for Colonization with Carbapenem-Resistant Microorganisms in Patients Admitted to a Multidisciplinary Hospital - O. G. Ni; B. Z. Belotserkovskiy; A. N. Kruglov; M. I. Matyash; A. O. Bykov; S. V. Yakovlev; E. M. Shifman; D. N. Protsenko (Эпидемиология и вакцинопрофилактика)
Relevance. In the last decade, there has been an increase in the isolation of antibiotic-resistant microorganisms in community settings. Colonization and asymptomatic carriage of extended-spectrum beta-lactamase and carbapenemase producers can be a precursor to the development of an infectious process and a significant factor in the pathogenesis of healthcare-associated infections. Understanding the risk factors for community-acquired colonization with antibiotic-resistant microorganisms is necessary for targeted screening and timely implementation of measures to prevent the spread of resistance in hospitals.The aim. To determine significant risk factors for colonization with antibiotic-resistant gram-negative microorganisms and carriage of carbapenem resistance genes in patients admitted to a multidisciplinary hospital.Materials & Methods. A prospective single-center crosssectional study was conducted at the Moscow Multidisciplinary Clinical Center «Kommunarka» from 15.09.2022 to 15.08.2023. The study included 733 patients aged 18 to 94 years. Biological samples were taken from the rectum, upper and lower respiratory tract. The obtained samples were examined by real-time polymerase chain reaction (PCR) with hybridization-fluorescent detection of amplification products to identify carbapenemase genes and by culture method to determine colonization with carbapenemresistant bacteria. Identification of isolated microorganisms was performed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), and antibiotic susceptibility was determined by the Kirby-Bauer disk diffusion method on Mueller-Hinton agar. The results of susceptibility testing were interpreted based on EUCAST v12.0, v13.0, and v13.1 criteria.Results. Carriage of carbapenemase genes was detected in 12.6% of patients admitted to the hospital, while colonization with carbapenem-resistant bacteria was found in 2.7%. In the majority of patients (66.7%), the rectum was the only site of gene carriage. However, only 18.1% of these patients showed rectal colonization with carbapenem-resistant bacteria. This discrepancy is likely due to the higher sensitivity of molecular genetic methods compared to culture-based techniques. From a clinical perspective, the detection of nucleic acids by PCR can serve as an equivalent to pathogen detection in biological material. Multivariate analysis identified 5 independent predictors of colonization: cytostatic therapy, transfer from another hospital, need for vasopressor support, antibiotic use in the previous 3 months, and male gender.Conclusion. The identified risk factors allow for the identification of a highrisk patient cohort for targeted screening, enabling timely administration of appropriate antibiotic therapy and implementation of measures to prevent the spread of carbapenem resistance in the hospital.